PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI KEPALA SEKOLAH TERHADAP MOTIVASI BERPRESTASI GURU SEKOLAH DASAR NEGERI SEMPARUK - Yuliati Yuliati; H. M. Chiar; M. Syukri (Universitas Tanjungpura, 2021)
ABSTRACTThis research aims to determine the effect of transformational leadership and principalcommunication on the achievement motivation of SDN teachers in Semparuk Districtpartially or jointly. This research uses a quantitativ approach with a descriptive method.The measuring instruments used in this research are transformational leadershipinstruments, principals' communication instruments and achievement motivationinstruments using a Likert scale. Hypothesis testing was carried out in this research usingsimple and multiple regression techniques. The main finding in this research is thatpartially there is a positive influence of transformational leadership and principalcommunication on teacher achievement motivation. In the F test found a significancevalue of 0.000 <0.05 and an R2 value of 0.587, meaning that Ha is accepted proving thatthere is a positive and significant influence together with transformational leadership(X1) and principal communication (X2) on teacher achievement motivation (Y) of 58,7%.The conclusion of this research is that there is a positive influence of transformationalleadership on teacher achievement motivation, there is an influence of principalcommunication on teacher achievement motivation, and there is an inf luence oftransformational leadership and principal communication on teacher achievementmotivation of 58,7%.Keywords: Transformational Leadership, Communication, Achievement Motivation